Associations Between Pain drawing and Psychological Characteristics of Different Body Region Pains. Issue 4 (27th February 2014) - Hayashi, Kazuhiro; Arai, Young‐Chang P.; Morimoto, Atsuko; Aono, Shuichi; Yoshimoto, Takahiko; Nishihara, Makoto; Osuga, Tomoaki; Inoue, Shinsuke; Ushida, Takahiro
Abstract Background Pain drawings have frequently been used for documentation of pain and a convenient diagnosis tool. Pain drawings were found to be associated with psychological states in chronic patients with low back pain. Few researchers have investigated pain drawings except in low back pain. The aim of this study was to investigate the pain, pain drawings, psychological characteristics, and pain interference in the head, neck–shoulder (NS), and low‐back/lower‐limb (LB‐LL) regions among patients with chronic pain. Methods We included a total of 291 patients with new chronic pain (headache, 62; NS pain, 87; LB‐LL pain, 142). The pain drawings and scores of 10‐cm Visual Analogue Scale (VAS), Hospital Anxiety and Depression Scale (HADS), Pain Catastrophizing Scale (PCS), Short‐Form McGill Pain Questionnaire (SF‐MPQ), and Pain Disability Assessment Scale (PDAS) were extracted from medical records. A subset of 60 pain drawings was scored by senior and junior evaluators to assess inter‐rater agreement. We investigated the correlation between pain drawings and VAS, HADS, PCS, SF‐MPQ, and PDAS in each body region group at the initial visit. Moreover, almost all patients received nonsurgical treatment as a follow‐up and were investigated using VAS after treatment. Results The reliability of pain drawings was substantial with an interevaluator reliability in headache, NS, and LB‐LL pain. Nonorganic pain drawings were associated with psychological disturbances in NS and LB‐LL pain, but not headache. Poor outcomes were associated with nonorganic drawings in LB‐LL pain, but not in the case of headache or NS pain. Conclusions Our results suggest that the characteristics of patients with nonorganic drawings differ according to body regions.